Pembinaan Masyarakat dalam Pemanfaatan Limbah Sampah di Bank Sampah Prabumulih - Romadoni, Romadoni; Tahyuddin, Didi (Journal of Nonformal Education and Community Empowerment, 2018)
This study aims to determine the community development in the utilization of waste in Bank Sampah Prabumulih. This study used descriptive qualitative method. Data collection technique research using observation, interviews, and documentation. The result of the research shows that the development of waste utilization by Bank Sampah Prabumulih is one of the forms of environment based empowerment. From the development done to make people care about the environment, increasing knowledge of the community, the growing caring attitude, and increasing skills in utilizing waste. Suggestion from this research is Bank Sampah Prabumulih need to improve skill result from waste processing both in quality and quantity.